What is the best strategy for retaining gestures in working memory?. Issue 6 (2nd July 2016) - Gimenes, Guillaume; Pennequin, Valérie; Mercer, Tom
Abstract : This study aimed to determine whether the recall of gestures in working memory could be enhanced by verbal or gestural strategies. We also attempted to examine whether these strategies could help resist verbal or gestural interference. Fifty-four participants were divided into three groups according to the content of the training session. This included a control group, a verbal strategy group (where gestures were associated with labels) and a gestural strategy group (where participants repeated gestures and were told to imagine reproducing the movements). During the experiment, the participants had to reproduce a series of gestures under three conditions: "no interference", gestural interference (gestural suppression) and verbal interference (articulatory suppression). The results showed that task performance was enhanced in the verbal strategy group, but there was no significant difference between the gestural strategy and control groups. Moreover, compared to the "no interference" condition, performance decreased in the presence of gestural interference, except within the verbal strategy group. Finally, verbal interference hindered performance in all groups. The discussion focuses on the use of labels to recall gestures and differentiates the induced strategies from self-initiated strategies.